Answer:
(–∞, -4)
Step-by-step explanation:
Then we will multiply both sides of the equation by 2 π :
x + π ( 1 - x ) = 0
x + π - π x = 0
x ( 1 - π ) = - π / · ( - 1 )
x ( π - 1 ) = π
x = π / ( π - 1 )
In triangle ABC,
AC = 12/ (sin30) = 12 / (1/2) = 24
DC = 24-x
DB = DC tan 30 = (24-x) tan30 <span>=(24−x)/</span><span>√3
</span>
In triangle ADB using Pythagorean Theorem<span><span>x2</span>+((24−x)/<span>√3</span><span>)2</span>=<span>12^2</span></span><span><span>x2</span>+(24−x<span>)^2</span>/3=<span>12^2</span></span><span>3<span>x2</span>+(24−x<span>)^2</span>=432</span><span>4<span>x2</span>−48x+576=432</span><span>4<span>x2</span>−48x+144=0</span><span><span><span>x2</span>−12x+36=0
x1 = x2 =6
AD = AC - DC = 24- (24-x) = 6</span></span>
Answer:
Math
Step-by-step explanation:
Answer: y=−12x+3.
Step-by-step explanation: